Ssp1 CaMKK: A Sensor of Actin Polarization That Controls Mitotic Commitment through Srk1 in Schizosaccharomyces pombe - Gómez-Hierro, Alba (Public Library of Science, 2015)

(untitled) (PLoS One)
BACKGROUND: Calcium/calmodulin-dependent protein kinase kinase (CaMKK) is required for diverse cellular functions. Mammalian CaMKK activates CaMKs and also the evolutionarily-conserved AMP-activated protein kinase (AMPK). The fission yeast Schizosaccharomyces pombe CaMKK, Ssp1, is required for tolerance to limited glucose through the AMPK, Ssp2, and for the integration of cell growth and division through the SAD kinase Cdr2. RESULTS: Here we report that Ssp1 controls the G2/M transition by regulating the activity of the CaMK Srk1. We show that inhibition of Cdc25 by Srk1 is regulated by Ssp1; and also that restoring growth polarity and actin localization of ssp1-deleted cells by removing the actin-monomer-binding protein, twinfilin, is sufficient to suppress the ssp1 phenotype. CONCLUSIONS: These findings demonstrate that entry into mitosis is mediated by a network of proteins, including the Ssp1 and Srk1 kinases. Ssp1 connects the network of components that ensures proper polarity and cell size with the network of proteins that regulates Cdk1-cyclin B activity, in which Srk1 plays an inhibitory role.